Effect of cognitive loading on single-leg jump landing biomechanics of elite male volleyball players - Amoli, S. M.; Ataabadi, P. A.; Letafatkar, A.; Wilkerson, G. B.; Mansouri, M. B. (International Journal of Athletic Therapy & Training, 2021)
Anterior cruciate ligament (ACL) injury is prevalent during the single-leg jump landing in various sports. The effects of cognitive loading and how it affects risk of ACL injury are not well understood. The purpose of this study is to examine how landing kinetics change in the presence of cognitive loading during a volleyball block. Cognitive loading decreased activations in vastus lateralis and rectus femoris, and increased activation in biceps femoris and medial gastrocnemius muscles. During landing, the first and second peaks of ground reaction forces were 13% and 11% lower under cognitive loading, suggesting that cognitive loading alters landing biomechanics and muscle activations.